Chiral and effective U(1)A symmetry restoration in QCD - Braun, Jens; Leonhardt, Marc; Pawlowski, Jan M.; Rosenblüh, Daniel (Arxiv, 2020)
The nature and location of the QCD phase transition close to the chiral limit restricts the phase structure of QCD with physical pion masses at non-vanishing density. At small pion masses, explicit U (1)A-breaking, as induced by a non-trivial topological density, is of eminent importance. It triggers the 't Hooft interactions and also manifests itself in the interplay of four-quark interactions at low momentum scales. In the present work, we perform a Fierz-complete analysis of the emergence of four-quark interactions from the QCD dynamics at finite temperature, subject to a given 't Hooft coupling at large momentum scales. The variation of the latter allows us to test the robustness of our findings. Taking an estimate of the effect of the topological running of the 't Hooft coupling into account, our analysis suggests that the chiral transition in QCD with two massless quark flavours falls into the O(4) universality class.